Acute Kidney Injury After Craniotomy Is Associated With Increased Mortality: A Cohort Study. Issue 3 (28th November 2015) - Kovacheva, Vesela P.; Aglio, Linda S.; Boland, Torrey A.; Mendu, Mallika L.; Gibbons, Fiona K.; Christopher, Kenneth B.
Abstract: BACKGROUND: Acute kidney injury (AKI) is a serious postoperative complication. OBJECTIVE: To determine whether AKI in patients after craniotomy is associated with heightened 30-day mortality. METHODS: We performed a 2-center, retrospective cohort study of 1656 craniotomy patients who received critical care between 1998 and 2011. The exposure of interest was AKI defined as meeting RIFLE (Risk, Injury, Failure, Loss of Kidney Function, and End-stage Kidney Disease) class risk, injury, and failure criteria, and the primary outcome was 30-day mortality. Adjusted odds ratios were estimated by multivariable logistic regression models with inclusion of covariate terms thought to plausibly interact with both AKI and mortality. Additionally, mortality in craniotomy patients with AKI was analyzed with a risk-adjusted Cox proportional hazards regression model and propensity score matching as a sensitivity analysis. RESULTS: The incidences of RIFLE class risk, injury, and failure were 5.7%, 2.9%, and 1.3%, respectively. The odds of 30-day mortality in patients with RIFLE class risk, injury, or failure fully adjusted were 2.79 (95% confidence interval "CI", 1.76-4.42), 7.65 (95% CI, 4.16-14.07), and 14.41 (95% CI, 5.51-37.64), respectively. Patients with AKI experienced a significantly higher risk of death during follow-up; hazard ratio, 1.82 (95% CI, 1.34-2.46), 3.37 (95% CI, 2.36-4.81), and 5.06 (95% CI, 2.99-8.58), respectively, fully adjusted. In a cohort of propensity score-matched patients, RIFLE class remained a significant predictor of 30-day mortality. CONCLUSION: Craniotomy patients who suffer postoperative AKI are among a high-risk group for mortality. The severity of AKI after craniotomy is predictive of 30-day mortality.